Travail collaboratif et interactions dans les forums de discussion fermés. Cas d'élèves ingénieurs tunisiens - Yassine Jelmam (Université de Provence, 2010)
E-Learning uses new and unconventional teaching methods because of its own structure. In this structure teachers and students are not grouped in a class and the virtual "replace" the real. To be operational this new teaching method requires interaction between different actors and proposes chat rooms, e-mail and discussion forum as alternatives to classical classroom interactions. But what happens in the reality? How can we sure these tools are efficient to ensure a good learning? The empirical research in this paper gathered 52 students to set up a working group drawn from a discussion forum. We followed their exchanges to show that interactions between learners are responsible for sharing, collaboration and co-construction of knowledge.